The Interaction of the Holy Qur'an with the World - Hafiz Salmanul Farizy (Penerbit Hellow Pustaka, 2024)
The Holy Qur'an has played a significant role in shaping human society. In a time when ignorance and superstitions prevailed, the Qur'an emerged as a beacon of knowledge, culture, and dignity. Through the teachings of the Messenger of Allah, spirituality, education, and literacy reached new heights. The depth and sophistication of the Qur'anic teachings have the ability to impress any intellect. Revealed in a society plagued by injustice, the Qur'an, as the word of the Lord of the Universe, transformed a society living in ignorance into a model for the world,. The Prophet used the Qur'an to guide people towards virtue. Historical accounts demonstrate that the Qur'an emphasizes the importance of considering the thoughts and feelings of others when engaging in preaching and outreach activities. For instance, the speech delivered by the Muslim leader Ja'far bin Abitwalib in the presence of Quraysh leaders to secure the release of Muslims who had migrated to Ethiopia accurately reflects the moral and human transformations brought about by the Prophet (PBUH) in Arabia. According to the perspective presented in the Qur'an, the fundamental worldview of humanity was cantered on 'Tawhid'. All genuine religious doctrines share commonalities. Minor variations may exist in the specifics of traditions and practices. Religions were established by imparting the essence of God, such as duality, trinity, and plurality. One of the objectives of the Qur'an is to structure human existence on a foundation of ethics, fostering harmony between human life and other forms of life.